Effects on overall performance of feeding commercially grown pigs less or more than their lysine requirement in early and late finishing - Main, R.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1154 gilts (PIC L337 × C22, initially 72.3 ± 1.7 lb) were used to determine effects on subsequent growth performance of feeding less than or at the estimated lysine requirement for optimal growth and feed efficiency in early finishing (70 to170 lb). From d 0 to 27 and d 27 to 55, pigs were fed a diet containing 2.75 and 2.25 g lysine/Mcal ME, respectively, which was less than their estimated requirement. Pigs fed at their estimated requirements were provided diets containing 3.30 and 2.75 g lysine/Mcal ME from d 0 to 27 and 27 to 55, respectively. Pigs within each early finishing treatment subsequently were fed less than, at, or more than (1.75, 2.25, 2.75 g lysine/Mcal ME, respectively) the estimated lysine requirement from 170 lb to slaughter at 255 lb. In early finishing (70 to 170 lb), pigs fed at the estimated lysine requirement had improved (P<0.003) ADG, feed efficiency, and income over marginal feed costs (IOMFC) compared with those of pigs fed less than their estimated dietary lysine requirement. But pigs fed less than the lysine requirement had lower (P<0.001) feed cost per pound of gain. In late finishing (170 to 255 lb), ADG, feed efficiency, feed cost per pound of gain, and IOMFC improved (quadratic, P<0.006) with increasing dietary lysine, and were optimized at the estimated lysine requirement (2.25 g lysine/Mcal ME). Pigs fed lysine-deficient diets in early finishing had improved (P<0.005) feed efficiency and feed cost per pound of gain in late finishing, compared with those of pigs fed adequate lysine in early finishing. Carcass lean measures improved (quadratic, P<0.02) with increasing dietary lysine in late finishing. Feed costs per pound of gain from d 0 to 104 were increased (P<0.001) when feeding increased dietary lysine in early finishing, and were not affected (P>0.17) by late finishing dietary treatment. Overall IOMFC was not affected (P>0.62) by the lysine-to-calorie ratio (g lysine/Mcal ME) fed in early finishing (70 to 170 lb), and increased (linear, P<0.02) with increasing lysine in late finishing (170 to 255 lb). But increasing dietary lysine from 2.25 to 2.75 g lysine/ Mcal ME in late finishing did not improve (P>0.89) d 0 to 104 IOMFC. Due to compensatory improvements in late finishing feed efficiency and feed cost per pound of gain, pigs fed diets less than biological requirements in early finishing, and subsequently fed at the estimated lysine requirement in late finishing, had lower (0.145 vs. 0.148 ± $0.001, P<0.03) feed cost per pound of gain, and similar IOMFC (79.62 vs. 79.13 ± $ 0.62 per head, P>0.70) to that of pigs fed at the estimated dietary lysine requirement throughout finishing. Understanding the biologic and economic dynamics of over- and under-feeding lysine in early (70 to 170 lb) and late (170 lb to 255 lb) finishing provides guidance in formulating cost-effective feeding strategies. This study suggests that, as long as lysine requirements are being met in mid-late finishing (170 lb to slaughter), feeding slightly less than the lysine requirement for optimal performance in early finishing reduces feed costs without sacrificing overall IOMFC.
Keywords: Compensatory Gain; Lysine; Pigs; Swine